2013
DOI: 10.1111/codi.12022
|View full text |Cite
|
Sign up to set email alerts
|

Subspecialist emergency management of diverticulitis is associated with reduced mortality and fewer stomas

Abstract: Emergency management of diverticulitis by subspecialist colorectal surgeons is associated with low overall and operative mortality whilst safely achieving high rates of primary anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 21 publications
0
21
1
1
Order By: Relevance
“…Boyce et al in 2013 studied the impact of introducing a regional emergency subspecialty colorectal unit in Scotland and found that colorectal surgeons were more likely to perform primary anastomosis after emergency resection than general surgeons (68.4 versus 41.6%, P < 0.0001). 16 The emergency operative intervention rate was signifi-cantly higher than our study at 27%. This may be attributed to a more aggressive operative approach during their study time period.…”
Section: Discussioncontrasting
confidence: 66%
“…Boyce et al in 2013 studied the impact of introducing a regional emergency subspecialty colorectal unit in Scotland and found that colorectal surgeons were more likely to perform primary anastomosis after emergency resection than general surgeons (68.4 versus 41.6%, P < 0.0001). 16 The emergency operative intervention rate was signifi-cantly higher than our study at 27%. This may be attributed to a more aggressive operative approach during their study time period.…”
Section: Discussioncontrasting
confidence: 66%
“…Biondo and colleagues investigated the impact of surgical specialization on patients having emergency colorectal surgery, and concluded that specialization in colorectal surgery improved morbidity, mortality and complication rates. Boyce and co‐workers reported decreased mortality and complication rates in patients who had emergency operations for diverticulitis performed by surgeons with a colorectal special interest; however, there was no evidence of risk adjustment in their analysis.…”
Section: Discussionmentioning
confidence: 96%
“…18 It is interesting that these data suggest that 30-day mortality appeared significantly lower if emergency colonic resection is performed by subspecialist colorectal surgeons rather than non-colorectal specialists. Significantly better postoperative morbidity, 19,20 mortality, 20,21 stoma rate, 19,21 primary anastomosis rate 21 and anastomotic leak rate 20 have been reported previously for those emergency colorectal cases operated on by colorectal subspecialists. The unadjusted data from this study are best regarded as preliminary.…”
Section: Discussionmentioning
confidence: 55%